Effects of organosilicate structure on melt intercalation of thermoplastic polymers - Eo, T; Kim, S; Song, K; Kim, J (POLYMER SOC KOREA, 2000)
The effect of chain length and packing density of intercalated surfactants, annealing temperature, and annealing time on static melt intercalation of thermoplastic polymers was examined using x-ray and FTIR spectroscopy. Although melt intercalation of polymers was not successful when alkyl chains in organosilicates form a lateral monolayer structure, the type and structure of surfactants could not much affect final interlayer distances of most polymer/silicate hybrids. As annealing time increases, interlayer distance in organosilicates increases while the dispersity of the spacing between silicate layers decreases. However, the dispersity of interlayer spacing as well as interlayer distance in organosilicates increase with annealing temperature.
Keywords: MODIFIED LAYERED SILICATES; UNSATURATED POLYESTER; EPOXY NANOCOMPOSITES; MONTMORILLONITE; MODEL